GIS Mapping Analysis of Energy Consumption Patterns in Nepal - Sharma, Puspa (Geographical Journal of Nepal, 2009)
This paper is an attempt to use computerized GIS tool to visual portray of consumption of the main energy sources – firewood, electricity, kerosene and LPG at district level for the whole country into four levels. A series of tables have also been constructed to depict the average levels of consumption of those energy sources at regional levels. The consumption patterns are that the firewood consumption has dominated over all the energy sources, followed by kerosene, electricity and LPG. The firewood energy source is the largest and available throughout the country. This can be explained by the extensive forest coverage across the country, which is largest in the mountain districts. The consumption patterns of electricity and LPG are more or less the same for the ecological regions; with highest in the Tarai, while the mountain being the lowest. The country has huge water reserviour for generating hydro electricity, but its consumption shares nearly two and half less of the firewood, or half of the kerosene. The other two energy sources - kerosene and LPG are to be imported. Due to lack of time series data on household level energy consumptions, HDI has been taken to predict the energy consumptions in the future. It shows that the household proportion in consuming firewood will be decreased, signifying lessening burden on forest resource. On the other hand, the household consumption of hydro electricity will be increased, which will mean to increasing utilization of locally available water sources and reducing a huge amount of transportation cost incurred for distribution of kerosene and LPG particularly in the remote hill and mountain districts. But however, increasing projected consumption of LPG would require foreign currencies in the future. The Geographical Journal of Nepal, Vol. 7, 2009: 41-52